2021
DOI: 10.1016/j.acra.2021.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Resident Experiences With Virtual Radiology Learning During the COVID-19 Pandemic

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 19 publications
(38 reference statements)
0
24
0
2
Order By: Relevance
“…Although virtual communication was fundamental to safe operations during the pandemic, this approach is associated with limitations, including a perceived decrease in personalized teaching by some trainees and increased distractibility, yet many residents report a desire to maintain elements of virtual learning post-pandemic. 18 As immunization efforts continue to expand, residency training programs are slowly returning to a more traditional teaching structure. Based on the benefit and reported success of virtual online learning, we should consider which of the new methodologies should continue being employed, and with which modifications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although virtual communication was fundamental to safe operations during the pandemic, this approach is associated with limitations, including a perceived decrease in personalized teaching by some trainees and increased distractibility, yet many residents report a desire to maintain elements of virtual learning post-pandemic. 18 As immunization efforts continue to expand, residency training programs are slowly returning to a more traditional teaching structure. Based on the benefit and reported success of virtual online learning, we should consider which of the new methodologies should continue being employed, and with which modifications.…”
Section: Discussionmentioning
confidence: 99%
“…The most frequent barriers to attending this virtual curriculum were technical difficulties (43%) and childcare (36%). 18 …”
Section: Response To Covid-19mentioning
confidence: 99%
“… 18 For some residents, virtual readouts without real cases on a picture archiving and communication system (PACS) were also felt to be a training weakness. 9 Post-pandemic, virtual readouts may have a place in radiology training, but would likely exist in a hybrid model with in-person readouts 9 , 17 , 19 and would have to address the described disadvantages ( Table 1 ). Specifically, it would likely be helpful to initially establish a resident's level of knowledge and competence in-person due to the advantages of increased rapport and gauging body language, prior to taking advantage of a blended model through the use of a virtual platform.…”
Section: Readoutsmentioning
confidence: 99%
“… 4 , 7 , 8 One study that surveyed radiology residents showed the majority of residents were satisfied with the virtual delivery of teaching rounds. 9 For residents, remote rounds promotes social distancing and also reduces travel requirements which could decrease their time away from their current rotation. However, technical difficulties may impede learning and in general.…”
Section: Teaching Roundsmentioning
confidence: 99%
See 1 more Smart Citation